Editorial of Special Issue “Multiple Sclerosis: Diagnosis and Treatment II” - Victor M. Rivera (MDPI AG, 2021)
The special issue on Multiple Sclerosis: Diagnosis and Treatment II, reflects advances and discoveries in the molecular and cellular mechanisms of disease, and novel laboratory techniques providing more sensitivity to diagnostic techninques and the understanding of neuroinflammation. Mitochondrial-mediated apoptosis in isolated peripheral blood mononuclear cells and the role of reactive oxygen species are studied as indicators of activity of MS. In these cells, downregulation of circular and linera RNAs are reported as markers of highly active disease in MS. Progress and importance of Neurofilaments determinations in early diagnosis and as a marker of disease activity, and the analysis of the complex mechanisms and therapeutic potential of Sphingosine-1-phosphate receptor modulator are discussed. Epidemiologic observations from a highly diversified area of the world provide more insights into this important aspect of MS; discussions on the clinical challenges posed by spinal cord involvement in demyelinatind disorders and the latest aspects of pediatric onset MS, complement this fine collection of scientific papers.